Influence of socio-economic factors on the mental health of vulnerable populations at risk in Kakuma refugee camp - Harun, Aisha Zainab; Jerotich, Sum Tecla (Nairobi Journal of Humanities and Social Sciences, 2023)
The refugee experience is characterized by exposure in one's country of origin to numerous traumatic incidents during migration and daily stressors after settlement in the camps as a result of natural disasters, wars and persecution on the basis of their race, religion, political beliefs and social identity, who cannot rely on their country of origin to protect them. Although numerous studies on deaths, illnesses and physical traumas resulting from wars and disasters have been conducted, there are scanty longitudinal studies on how psychosocial issues influence mental health of vulnerable populations at risk and the problem-specific interventions used to address mental ill health. The prevalence of mental illnesses among refugees keeps increasing in spite existing psychiatric treatment options used to resolve the particular concerns associated with mental health. The objective of the study was to determine the influence of socio-economic factors on the mental health of vulnerable populations at risk in Kakuma refugee camp, Turkana County, Kenya.